From spawn to survival: decoding the hydraulic conditions for successful silver carp egg incubation - Xian-bing Zhang; Jia-fei Wang; Geng Li; Yu-peng Hu; Wei Yang; Wen-jie Li; Shan Yu (PLoS ONE, 2025)
Natural rivers exhibit complex and dynamic flow conditions that significantly influence the survival and development of semi-buoyant fish eggs. This study investigated the effects of flow velocities and turbulence on silver carp eggs (Hypophthalmichthys molitrix) during their development. Laboratory experiments conducted in an annular flume revealed that moderate flow conditions (0.5 m/s) yielded optimal hatching rates, while excessive velocities (1.1 m/s) led to complete mortality at the Late Blastula stage. Mild turbulence facilitated egg incubation, whereas intense turbulence reduced hatching success and increased larvae deformation rates. These findings revealed distinct relationship between hydrodynamic conditions and embryonic development, indicating that optimal spawning conditions differ from those required for successful hatching. These results provide fundamental insights for evaluating suitable hydraulic conditions in river habitats and assessing the potential impacts of hydraulic structures on fish populations. The study contributes valuable knowledge to river ecosystem management, semi-buoyant fish species conservation, and fish-friendly hydraulic structure design.